Analisis Yuridis tentang Pembunuhan yang dilakukan oleh Anggota TNI Angkatan Darat terhadap Warga Sipil - Arif Widodo; Setiyono Setiyono; Teguh Suratman; Nahdiya Sabrina (University of Merdeka Malang, 2023)
This research is motivated by the existence of cases of killings committed by elements of the Indonesian Army against civilians which is a serious violation that should not have been committed. The legal issues that will be analyzed in this study are knowing and explaining: the basic considerations of the judges in the decision of the Military Court III-12 Surabaya Number 223-K/PM.III-12/AD/XII/2018 decided on cases of deprivation of independence resulting in death by members of the TNI AD against civilians. The research method uses normative legal research in the form of legal behavior products by examining laws. The problem approach uses a normative juridical approach. The results of this study found that: The judge's consideration in the Decision of the Military Court III-12 Surabaya Number 223-K/PM.III- 12/AD/XII/2018 has fulfilled the elements of Article 333 paragraph (1) of the Criminal Code with a criminal sanction of 1 year 2 months and dishonorable dismissal; The decision of the II-12 Surabaya Military Court Number 223-K/PM.III-12/AD/XII/2018 has fulfilled a sense of justice, due to insufficient valid and convincing evidence of guilt for committing the crime of murder which was carried out jointly.